Impacts of heat decarbonization on system adequacy considering increased meteorological sensitivity. (15th September 2021) - Deakin, Matthew; Bloomfield, Hannah; Greenwood, David; Sheehy, Sarah; Walker, Sara; Taylor, Phil C.
Abstract: This paper explores the impacts of decarbonization of heat on demand and subsequently on the generation capacity required to secure against system adequacy standards. Gas demand is explored as a proxy variable for modelling the electrification of heating demand in existing housing stock, with a focus on impacts on timescales of capacity markets (up to four years ahead). The work considers the systemic changes that electrification of heating could introduce, including biases that could be introduced if legacy modelling approaches continue to prevail. Covariates from gas and electrical regression models are combined to form a novel, time-collapsed system model, with demand-weather sensitivities determined using lasso-regularized linear regression. It is shown, using a Great Britain-based case study with one million domestic heat pump installations per year, that the sensitivity of electrical system demand to temperature (and subsequently sensitivities to cold/warm winter seasons) could increase by 50% following four years of heat demand electrification. A central estimate of 1.75 kW additional peak demand per heat pump is estimated, with variability across three published heat demand profiles leading to a range of more than 14 GW in the most extreme cases. It is shown that the legacy approach of scaling historic demand, as compared to the explicit modelling of heat, could lead to over-procurement of 0.79 GW due to bias in estimates of additional capacity to secure. Failure to address this issue could lead to £100m overspend on capacity over ten years. Highlights: System adequacy considered in context of transition to electrified heat. 30-year net demand hindcast based on Lasso regression and weather reanalysis data. GB temperature-demand sensitivity could increase by 54% in just 4 years. Electric heat demand growth uncertainty doubles variability in capacity to secure. Legacy modelling approach could lead to £100m over-procurement over 10 years.